Slash [videorecording (DVD)] - Johnston, Michael; Marks, Hanna H.; Abbott, Deborah (Gravitas Ventures, 2016)
15-year-old Neil loves the SciFi world of "Vanguard." The erotic fan fiction that it inspires him to write remains his deepest secret...until he meets Julia, who pushes him to publish online. This draws the attention of the internet at large and Denis, the moderator of a highly influential erotic website. When Denis invites Neil to present his fiction at a famous comic con, Neil is forced to confront a strange new world that he might not be ready for.